Kajian tranformasi dengan wavelet daubechies dan parameter thresholding-nya - Rahayu, Tika Sri; Saputro, Dewi Retno Sari (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
Along with the development of science and technology in the era of globalization continues to progress. In analyzing high fluctuating data, a method is needed to detect the signal, one of which is using the wavelet method. A wavelet is a transformation function that automatically cuts data into different parts and studies each component with a resolution appropriate to its scale. One type of wavelet is Daubechies wavelet. In analyzing wavelets there is noise that affects the accuracy of the data, so noise reduction process is needed using thresholding. The purpose of this research is to study the Daubechies wavelet transform and thresholding parameters. The result of this research is a study of the Daubechies wavelet method and the threshoding parameters, namely the minimax threshold and the universal threshold.